The Role of Endoplasmic Reticulum Stress Response in Pollen Development and Heat Stress Tolerance - Singh, Mohan B.; Lohani, Neeta; Bhalla, Prem L. (Frontiers in Plant Science, 2021)
Endoplasmic reticulum (ER) stress is defined by a protracted disruption in protein folding and accumulation of unfolded or misfolded proteins in the ER. This accumulation of unfolded proteins can result from excessive demands on the protein folding machinery triggered by environmental and cellular stresses such as nutrient deficiencies, oxidative stress, pathogens, and heat. The cell responds to ER stress by activating protective pathway termed unfolded protein response (UPR), which comprises cellular mechanisms targeted to maintain cellular homeostasis by increasing the ER's protein folding capacity. The unfolded protein response (UPR) is especially significant for plants as being sessile requires them to adapt to multiple environmental stresses. While multiple stresses trigger the UPR at the vegetative stage, it appears to be active constitutively in the anthers of unstressed plants. Transcriptome analysis reveals significant upregulation of ER stress related transcripts in diploid meiocytes and haploid microspores. Interestingly several ER stress-related genes are specifically upregulated in the sperm cells. The analysis of gene knockout mutants in Arabidopsis has revealed that defects in ER stress response lead to the failure of normal pollen development and enhanced susceptibility of male gametophyte to heat stress conditions. In this mini-review, we provide an overview of the role of ER stress and UPR in pollen development and its protective roles in maintaining male fertility under heat-stress conditions.